2018
DOI: 10.1002/jcb.27542
|View full text |Cite|
|
Sign up to set email alerts
|

Retracted: Curcumin derivative L6H4 inhibits proliferation and invasion of gastric cancer cell line BGC‐823

Abstract: Curcumin and its chalcone derivatives have well‐known, explicit biological antitumor properties, such as instance antiproliferative and apoptotic effects via multiple molecular targets. In this study, we investigated the anticancer activity of curcumin derivative L6H4 (curcumin L6H4) on gastric cancer cells. Inhibitory effects of curcumin L6H4 on gastric cancer cells (BGC‐823) were studied by the diphenyltetrazolium (MTT) assay, and cell apoptosis was detected by Annexin‐V/propidium iodide (PI) staining and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 24 publications
1
8
0
Order By: Relevance
“…In 2018, Mu et al tested the antiproliferative activity of compound L6H4 ( 22 , Figure 5 ) on gastric BGC-823 cancer cells [ 46 ]. The authors concluded that 22 was able to inhibit cell proliferation by inducing apoptosis and enhancing the expression levels of p53, p21, Bax, and Bcl-2, both in vitro and in vivo.…”
Section: Interference With P53 Pathway By Synthetic Chalconesmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2018, Mu et al tested the antiproliferative activity of compound L6H4 ( 22 , Figure 5 ) on gastric BGC-823 cancer cells [ 46 ]. The authors concluded that 22 was able to inhibit cell proliferation by inducing apoptosis and enhancing the expression levels of p53, p21, Bax, and Bcl-2, both in vitro and in vivo.…”
Section: Interference With P53 Pathway By Synthetic Chalconesmentioning
confidence: 99%
“…The expression of p53 was increased at 10 µM L6H4 ( 22 ) after 48 h in in vitro assays. On the other hand, in vivo studies on male BALB/c nude mice showed an increase of p53 levels after treatment with 15 µM L6H4 ( 22 ) for 48 h [ 46 ].…”
Section: Interference With P53 Pathway By Synthetic Chalconesmentioning
confidence: 99%
“…Many studies showed that curcumin has anti-oxidation, anti-growth, antiarthritic and anti-inflammation actions [ 6 ]. In particular, it has been reported that curcumin induces apoptosis, inhibits cell proliferation and migration in human leukemia, colon, prostate, renal and non-small-cell lung cancer [ 7 9 ], suggesting that it might be a novel agent for the prevention and treatment of ESCC.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, application of curcumin Light might be an innovative concept to accompany established RCC treatment protocols. The relevance of curcumin alone to act on tumor cell invasion has already been shown on other tumor entities, whereby curcumin concentrations of 10 µM, 15 µM, 50 µM, or higher have been applied to stop invasion of gastric [37], breast [38], prostate [39], or hepatic cancer cells [40]. Ongoing experiments should, therefore, deal with the question of whether the beneficial effects of light exposure on curcumin may also hold true for these tumor types.…”
Section: Discussionmentioning
confidence: 91%